Laparoscopic versus Open Splenectomy and Devascularization for Massive Splenomegaly Due to Portal Hypertension - 刘尧 赵龙 唐勇 张宇 施申超 谢付骁 万赤丹 (华中科技大学学报：医学英德文版, 2016)
Although the clinical benefit of laparoscopic splenectomy and devascularization(LSD) has been elaborated in many studies,its application in massive splenomegaly remains controversial.We conducted a retrospective research to assess the curative efficacy of LSD for massive splenomegaly due to portal hypertension.Forty-seven patients with massive splenomegaly due to portal hypertension were enrolled in this study,and divided into two groups.Twenty-one patients underwent open splenectomy and devascularization(OSD) from June 2010 to October 2012(OSD group).From March 2013 to February 2015,LSD was performed on 26 patients(LSD group).Perioperative variables were analyzed.Compared to OSD,LSD was associated with less blood loss(241.9±110.0 m L vs.319.0±139.5 m L,P<0.05),more rapid resumption of oral diet(2.46±0.95 days vs.3.76±1.09 days,P<0.05),and shorter postoperative hospital stay(5.35±1.65 days vs.7.24±1.55 days,P<0.05).It was concluded that for patients with massive splenomegaly due to portal hypertension,LSD is feasible and as safe as OSD.